Differences in The Psychological Condition of Teenagers Victims of Domestic Violence: Based Gender - Gusni Dian Suri; Afdal Afdal; Rezki Hariko; Miftahul Fikri; Mutia Afnida; Soeci Izzati Adlya; Denia Syapitri (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
Domestic violence in Indonesia is very concerning and has an impact on the psychological condition of teenagers, not only on victims. The impact of the psychological condition of teenagers victims of domestic violence, both boys and girls, namely short-term to long-term health, including aspects of physical conditions, emotional conditions, economic conditions, psychological impacts, and expectations on teenagers. This study aims to see the differences in the psychological conditions of boys and girls victims of domestic violence. Data were collected with the subject of teenagers victims of domestic violence selected by purposive sampling in West Sumatera through an instrument with psychological aspects. Data were analyzed using t-test. The results of statistical analysis of the group in this study consisted of 126 boys and 218 girls. Indicates that based on the difference in the mean value is 9.3571 for boys and 10.8532 for girls. Based on the interpretation of the independent sample t-test for the significance of the difference, the asymp. Sig. (2-tailed) is smaller than the significance level of 0.05 (0.009 < 0.05). This means that there is a significant difference between the psychological conditions of teenagers victims of domestic violence in boys and girls. Girls teenagers have a higher impact on psychological conditions than male teenagers. Statistical analysis using ANOVA sig value of 0.247>0.05 which means that there is a significant difference that age differences affect the psychological condition of child victims of domestic violence. The research findings can be an additional reference for teachers, especially school counselors or Guidance and Counseling teachers to provide services that suit the needs of the psychological conditions of teenagers girls and boys.